Enhancing Students’ Scientific Writing Competence in a Vocational Education Institution through Structured Training and Mentoring - Ramli Rasyid; Ishak Ishak; Ridwan Ridwan; Taufiq Natsir (PT. Global Research Collaboration, 2025)
Scientific writing is an essential competency for vocational students, enabling them to engage with academic literacy demands and adapt to the evolving expectations of the modern workforce. At SMKN 1 Tana Toraja, students’ scientific writing skills remain limited, as reflected in their difficulties understanding article structure, applying citation techniques, and conducting proper literature searches. This community service program was implemented to address these challenges through structured training combined with continuous mentoring. The program introduced participants to the fundamentals of academic writing, guided them in developing article outlines, provided instruction on identifying credible references, and trained them to use reference management tools such as Mendeley. Students also received step-by-step assistance in refining their drafts until completion. The learning approach emphasized hands-on practice, allowing participants to experience the writing process directly and progressively. Program effectiveness was assessed through pre-test and post-test evaluations, which revealed a 42% improvement in students’ conceptual understanding. Additionally, 78% of participants successfully completed scientific manuscripts that met expected academic standards. The program produced a digital writing module and audiovisual materials that can serve as sustainable learning resources. Overall, this initiative significantly strengthened students’ academic literacy skills and encouraged the development of a productive writing culture within the vocational education environment.